2016
DOI: 10.1177/1098300715599737
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sustained Implementation of School-Wide Positive Behavioral Interventions and Supports

Abstract: In this analysis of extant data from 3,011 schools implementing school-wide positive behavioral interventions and supports (SWPBIS) across multiple years, we assessed the predictive power of various school characteristics and speed of initial implementation on sustained fidelity of implementation of SWPBIS at 1, 3, and 5 years. In addition, we partitioned variance in whether schools sustained SWPBIS at the school, district, and state levels. Results showed that the largest differences in fidelity were at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 36 publications
7
64
1
Order By: Relevance
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).…”
Section: Community Settingssupporting
confidence: 92%
See 2 more Smart Citations
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).…”
Section: Community Settingssupporting
confidence: 92%
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).Several studies have focused on the sustainability of coalitions aimed at implementing EBIs, including the Communities That Care (CTC) coalition-based prevention system (51) and the PROSPER community-university partnership model (56). A study of 110 CTC sites in Pennsylvania found that 90% of coalitions continued after the three-year initial funding period, with 3-8% of sites terminating each year after (36).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Out of necessity, developers initially direct attention to expanding the number of new users ("adoption" of innovations). Over time, as the number of users increases, more attention must be paid to de-adoption and re-adoption (Massatti, Sweeney, Panzano, and Roth, 2008;McIntosh, Mercer, Nese, Strickland-Cohen, and Hoselton, 2015) while continuing to expand the numerator by developing new users. A container that is draining as fast as it is being filled simply maintains the same level.…”
Section: Numerator Moderatorsmentioning
confidence: 99%
“…Covariates Including good predictors of compliance can increase precision in estimating the latent class compliance variable and, therefore, increase power to detect CACE effects (Jo et al 2008b). Student-(gender, FSM eligibility, SEND, baseline reading scores, concentration problems, and disruptive behaviors) and school-level (size, FSM %, EAL %, absences %) characteristics were thus added as covariates of reading scores and the latent compliance variable, as research shows that implementation can be influenced by the classroom climate, and student-and school-level characteristics (Koth et al 2008;McIntosh et al 2016;Pas et al 2014;Payne and Eckert 2010). We paid particular attention to including predictors that were aligned with the behavioral focus of the GBG (Panayiotou et al 2019Nagengast et al 2018.…”
Section: Discussionmentioning
confidence: 99%